Determinants Of Tax Avoidance: A Study on Manufacturing Companies in The Food and Beverage Sector Across Six Southeast Asian Countries - Anissa Yuniar Larasati; Hartika, Wiwi (Universitas Pamulang, 2025)
The purpose of this study is to determine the effect of profitability, leverage, company size, and financial distress on tax avoidance in six Southeast Asian countries, namely Indonesia, Malaysia, Singapore, Thailand, the Philippines, and Vietnam. This study was measured using quantitative methods and secondary data. The sample measurement used purposive sampling and obtained 106 manufacturing companies from six countries in Southeast Asia during the period 2020-2023, resulting in a total of 424 observations in this study. Based on the test results using SPSS vs 26, it was found that profitability had a negative effect on tax avoidance. Leverage has a positive effect on tax avoidance. Meanwhile, company size and financial distress have no effect on tax avoidance. Simultaneously, profitability, leverage, company size, and financial distress affect tax avoidance.